Variable impact of prior cancer history on the survival of lung cancer patients. (January 2019) - Monsalve, Andres F.; Hoag, Jessica R.; Resio, Benjamin J.; Chiu, Alexander S.; Brown, Lawrence B.; Detterbeck, Frank C.; Blasberg, Justin D.; Boffa, Daniel J.
Highlights: 21.9% of Non-small cell lung cancer patients have a history of prior cancer. A prior cancer history appears to have variable impact on outcomes. Earlier-staged tumors are the most negatively impacted by prior cancer history. In 32.3% of patients, prior cancer diagnosis was associated with increased survival. Including patients with prior cancer history in prospective studies should account for the heterogenous survival effect. Abstract: Introduction: Non-Small Cell Lung Cancer (NSCLC) is commonly diagnosed in patients who have survived a prior malignancy. However, it is currently unclear whether NSCLC patient survival is impacted by the potential for previously-treated malignancies to recur. Understanding the impact of a prior cancer history on NSCLC survival could not only enhance decision making but could affect eligibility for NSCLC studies. Methods: The National Cancer Database (NCDB) was queried for NSCLC patients (stage I–IV) diagnosed between 2004–2014. Kaplan-Meier survival curves and multivariable Cox proportional hazards regression models were estimated to analyze overall survival across a variety of treatment approaches and stages in the presence and absence of a prior cancer history. Results: A total of 821, 323 patients with a newly diagnosed NSCLC were identified including 179, 512 (21.9%) with a prior history of cancer. The unadjusted 5-year overall survival of patients with a prior cancer history (9.8%) was slightly better to those without a cancer history (9.5%, 95% CI 11.76–11.84, P < 0.0001). However, adjusted analyses revealed the impact of prior cancer history was extremely heterogenous across stage and treatment approach. Ultimately, 51.4% of patients fell into a subgroup in which prior cancer history appeared to compromise survival, 16.3% in which the difference was not significant, and 32.3% in which prior cancer was associated with increased survival. Patients with earlier-staged tumors were the most negatively NSCLC impacted by prior cancer history. Conclusions: The association between prior cancer history and survival of newly diagnosed NSCLC patients is highly variable and to some degree reflects a patient's potential for cure.